Gloss on the Judgment of Court of Justice of the European Union of 19 February 2002, Case C-309/99, J.C.J. Wouters, J.W. Savelbergh and Price Waterhouse Belastingadviseurs BV v. Algemene Raad van de Nederlandse Orde van Advocaten, Intervener Raad van de - Maria Lewandowicz; Agnieszka Piwowarczyk (Studia Prawa Publicznego)
In its judgment of February 19, 2002, in Case C-309/99 (Wouters), the Court of Justice of the European Union (CJEU) sanctioned the permissibility of the ban on the establishment of companies by lawyers together with chartered accountants. At the same time, the provisions of the 1993 Dutch Samenwerk- ingsverordening, which prohibits any kind of integrated cooperation between attorneys and chartered accountants, were found not to be in conflict with Article 101 TFEU (then Article 81 TEC). This is because a prohibition of this nature has been recognized by the CJEU as necessary for the proper practice of the legal profession as it is organized in a member state – in this case, the Neth- erlands. In Poland, chartered accountants are a profession of public trust, and thus there are no grounds for maintaining a prohibition on the establishment    of partnerships of attorneys and chartered accountants.